Know yourself and take charge of your own destiny: the "fit model" of leadership - Hanbury, George L.; Washington, Charles W.; Sapat, Alka (2004)
Leadership scholars have theorized that leaders of an organization must have an appropriate "fit" with those they lead and with their environment. Yet, there is no empirical research to date that has explored this belief. we develop a theoretical model to determine the factors influencing the fit of a city manager, indicated by his or her tenure. We argue that six sets of explanations may help determine the fit of the city manager: the manager's leadership style, his or her personality type, the city manager's perception about fit, the perceptions of city councils, the demographics of the city managers, and the demographics of the cities where they work. Based on a rigorous nation-wide study of city managers, the study shows that the fit of city managers is significantly influenced by two of the six sets of explanations. Implications for scholars, city managers, and practitioners are drawn from the study's analysis and findings. - Reproduced.
Keywords: Leadership